Effects of Illustrated Glossary of Plant World Material on Students Creative Thinking Ability - Purnama, Egi; Suryawati, Evi; Zulfarina, Zulfarina (Journal of Educational Sciences, 2020)
This study aims to look at the effect of pictorial glossaries on the creative thinking abilities of class X students, SMAN 1 Teluk Kuantan on the subject of the Plant World. This type of research was quasi-experimental research. The study population was all high school grade X students as a hypothetical population. The research sample consisted of 67 people consisting of 33 students in class X MIPA 1 as a control class and 34 students in class X MIPA 2 as an experimental class. Data collection techniques used observation sheets. The result shows that average score of the creative thinking ability of the control class students obtained a mean of 64 with a moderate category while the experimental class obtained an average of 74 with a high category. This shows the influence of glossary media in the material world of plants in SMAN 1 Teluk Kuantan with a significant level of 0.05. Thus, there is an influence of the use of pictorial glossaries on the creative thinking abilities of the control class students with the experimental class on plant material in the learning process.